The “perfect” storm: Current evidence on pediatric inflammatory multisystem disease during SARS-CoV-2 pandemic: COVID19 and pediatric inflammatory multisystem disease - Lami, Francesca; Scalabrini, Ilaria; Lucaccioni, Laura; Iughetti, Lorenzo (Acta Biomedica Atenei Parmensis, 2020)
Current data suggest that during the global pandemic of COVID 19 children are less affected than adults and most of them are asymptomatic or with mild symptoms. However, recently, cases of pediatric patients who have developed severe inflammatory syndrome temporally related to SARS-CoV-2 have been reported both in USA and Europe. These reports, although sharing features with other pediatric syndromes such as Kawasaki disease (KD), Kawasaki disease shock syndrome (KDSS), macrophage activated syndrome (MAS) and shock toxic syndrome (TSS), seem to outline a novel entity syndrome, characterized by cytokine storm with elevated inflammatory markers and typical clinical finding. Clinical characteristics are greater median age than KD, higher frequency of cardiac involvement and gastrointestinal symptoms, lower frequency of coronary anomalies. We report a summary of the current evidence about clinical features, pathogenesis, therapy strategies and outcome of this novel syndrome.